Connecting the Dots: Effects of Close Reading on Students' Comprehension of Primary Sources - Ballance, Ann Marie (East Carolina University, 2016)
The Common Core State Standards require teachers to incorporate more primary sources in the history classroom. Primary source documents are often challenging, so teachers must find strategies to help students analyze them. Close reading has been used to help students comprehend primary sources. This strategy causes students to read more slowly and address challenging passages (Fisher, Brozo, Frey, & Ivey, 2015). The present study occurred at a high school in eastern North Carolina. The participants included tenth graders in two Civics and Economics classes. The researcher implemented a single-group interrupted time-series design over four weeks, where she taught participants a close reading strategy using different primary sources. Then, the participants completed a reading comprehension instrument developed by the researcher, which was evaluated using corresponding rubrics. Following this, the researcher analyzed data using descriptive statistics to compare changes in reading comprehension and close reading scores. Throughout the study, researcher also kept a field journal and conducted a qualitative analysis of participant responses. There were no significant changes in reading comprehension throughout the study, but the close reading scores suggested that participants did not transfer the strategy effectively.
Keywords: history teaching; history education; disciplinary literacy; history and reading; reading strategies; content area reading